Bacteriophage growth on stationary phase achromabacter strains - Robb, Susan Mary (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1980)
Achromobacter w.t. and strain 14 both support phage Î±3a growth in stationary phase, but unlike the w.t. strain, exponential phase cultures of strain 14 block phage development. A standard method was developed for determining phage growth in stationary phase cultures. Lyophilised cells were used to eliminate variations due to the unstable phenotype of Achromobacter strain 14 cells. Phage Î±3a growth in stationary phase was characterized by a long and variable latent period of 6 to 9 h and an increased burst size of 709 p.f.u. per cell as compared with 153 p.f.u. per cell in exponential wild type cells. During the latent period the infected cells were very sensitive to changes in growth conditions and in particular, dilution. Pre-conditioning of the bacterial cells by allowing them to stand for 24 h after shaking for 3 days was an important aspect of the stationary phase phage growth system. Cells which had been allowed to stand retained the ability to be infected and to support phage growth for at least 16 days. Shaking cultures gradually lost the ability to support phage growth but the phage could persist in the host cell for 10 days until removal from shaking when the lytic cycle could proceed after allowing the cultures to stand. In comparison the latent period and burst size in Achromobacter w.t. stationary phase cells were reduced to less than 2 h and less than 200 respectively. Stationary phase cultures differed physiologically and morphologically depending on the aeration conditions. In comparison with non-aerated standing cultures, vigorously aerated cultures showed a decrease in viability, RNA synthesis, membrane transport, intracellular ATP levels, UV resistance and heat resistance but had markedly higher protein synthesis levels. Aerated cells were small non-motile rods which did not support phage growth. They developed into large motile rods under conditions of limited aeration and were able to propagate phage. It was proposed that changes in the host control mechanisms for macromolecular synthesis may be instrumental in either blocking or permitting phage development. A spontaneous mutant of Achromobacter strain 14 (14x) which liberated phage and was resistant to superinfection was isolated. The phage-host relationship was unstable and similar to the phage carrier state. The liberated phage were able to grow in exponential strain 14 cells. It was proposed that strain 14 was a defective lysogen and that an immunity phase shift model may account for the differential phage growth in exponential and stationary phase cells. Host transcriptional control appears to be implicated in control of phage development in exponential and stationary phase cells. Achromobacter Lp only supported phage in exponential phase but a rifampicin resistant mutant of this strain was able to propagate phage in stationary phase. In vitro RNA synthesis assays showed that the rifampicin resistance was caused by an alteration in the RNA polymerase. Preliminary experiments to determine intracellular phage macromolecular synthesis were carried out using exponential Achromobacter w.t. cells which had been irradiated with UV prior to infection. In irradiated cells, infection with phage resulted in stimulation of DNA synthesis but no stimulation of protein synthesis. Phage production was drastically reduced in cells which had been treated with very low UV doses. It was proposed that Î±3a development may rely heavily on host cell functions which are destroyed by UV. Achromobacter mutants with defective leucine transport systems were isolated. Mutants which lost the leucine uptake system completely were totally resistant to phage infection and were unable to adsorb phage Î±3a. This is the first report to implicate an amino-acid transport system in phage adsorption.
Keywords: Bacteriophages; Strains and stresses